Smart and Sustainable: Transportation’s Evolving Role in Enhancing Regional Economic Outcomes - Muharam, Husni; Wufron, Wufron (Yayasan Sinergi Kawula Muda, 2023)
This study aims to examine the evolving role of transportation—particularly smart and sustainable transport systems—in fostering regional economic development. Transportation plays a critical role in shaping regional economies by facilitating trade, enhancing mobility, and fostering spatial equity. By employing a narrative review approach, this study synthesizes empirical findings and global case comparisons to highlight how investments in smart transportation technologies and sustainability-oriented practices can enhance economic performance. Findings reveal that investments in transportation infrastructure—particularly high-speed rail, multimodal systems, and intelligent transport networks—drive economic expansion, improve accessibility, and reduce regional disparities. Technological innovations, stakeholder engagement, and sustainability-oriented policies further enhance the economic impact of transport systems. However, the review identifies persistent challenges, including funding limitations, governance inefficiencies, socio-spatial inequalities, and environmental trade-offs. It also highlights systemic barriers such as political fragmentation, resource misallocation, and cultural perceptions that hinder transport utilization. Lessons from global case studies demonstrate that tailored, inclusive, and adaptive strategies are essential for maximizing transportation's economic potential. The review concludes with policy recommendations that emphasize integrated planning, sustainable practices, and data-driven interventions. Future research should explore longitudinal outcomes, demographic-specific impacts, and localized behavioral insights to inform more effective and equitable transport policies.